Estimates of cancer burden in Abruzzo and Molise. Issue 3 (May 2013) - Foschi, Roberto; Viviano, Lorena; Rossi, Silvia
Aims and background: Abruzzo and Molise are two regions located in the south of Italy, currently without population-based cancer registries. The aim of this paper is to provide estimates of cancer incidence, mortality and prevalence for the Abruzzo and Molise regions combined. Methods: The MIAMOD method, a back-calculation approach to estimate and project the incidence of chronic diseases from mortality and patient survival, was used for the estimation of incidence and prevalence by calendar year (from 1970 to 2015) and age (from 0 to 99). The survival estimates are based on cancer registry data of southern Italy. Results: The most frequently diagnosed cancers were those of the colon and rectum, breast and prostate, with 1, 394, 1, 341 and 698 new diagnosed cases, respectively, estimated in 2012. Incidence rates were estimated to increase constantly for female breast cancer, colorectal cancer in men and melanoma in both sexes. For prostate cancer and male lung cancer, the incidence rates increased, reaching a peak, and then decreased. In women the incidence of colorectal and lung cancer stabilized after an initial increase. For stomach and cervical cancers, the incidence rates showed a constant decrease. Prevalence was increasing for all the considered cancer sites with the exception of the cervix uteri. The highest prevalence values were estimated for breast and colorectal cancer with about 12, 300 and over 8, 200 cases in 2012, respectively. In the 2000s the mortality rates declined for all cancers except skin melanoma and female lung cancer, for which the mortality was almost stable. Conclusion: This paper provides a description of the burden of the major cancers in Abruzzo and Molise until 2015. The increase in cancer survival, added to population aging, will inflate the cancer prevalence. In order to better evaluate the cancer burden in the two regions, it would be important to implement cancer registration.